2021
DOI: 10.1002/etc.5111
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Ecosystem Fluxes of Pesticides from Prairie Wetlands Mediated by Aquatic Insect Emergence: Implications for Terrestrial Insectivores

Abstract: Contaminants alter the quantity and quality of insect prey available to terrestrial insectivores. In agricultural regions, the quantity of aquatic insects emerging from freshwaters can be impacted by insecticides originating from surrounding croplands. We hypothesized that, in such regions, adult aquatic insects could also act as vectors of pesticide transfer to terrestrial food webs. To estimate insect-mediated pesticide flux from wetlands embedded in an important agricultural landscape, semipermanetly and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 88 publications
2
18
0
Order By: Relevance
“…The estimated value is however considerably lower than what has been observed in field studies, where estimates of daily fluxes of insecticides from wetlands are between 0.4 and 26.8 ng/m 2 •d, when also including other aquatic insect orders. 9 The specific contributions of midges in this context are, however, of relevance considering that Chironomidae are the most abundant and have the longest emergence window among the common emerging insect orders, thus making them an important nutrient source in terrestrial food webs. 61,63 Moreover, aquatic insect communities in polluted aquatic environments often show a shift toward dipterans dominating the remaining insect fauna due to their tolerance of a wide range of anthropogenic disturbances, for example, in aquatic environments disturbed by agriculture.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated value is however considerably lower than what has been observed in field studies, where estimates of daily fluxes of insecticides from wetlands are between 0.4 and 26.8 ng/m 2 •d, when also including other aquatic insect orders. 9 The specific contributions of midges in this context are, however, of relevance considering that Chironomidae are the most abundant and have the longest emergence window among the common emerging insect orders, thus making them an important nutrient source in terrestrial food webs. 61,63 Moreover, aquatic insect communities in polluted aquatic environments often show a shift toward dipterans dominating the remaining insect fauna due to their tolerance of a wide range of anthropogenic disturbances, for example, in aquatic environments disturbed by agriculture.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During their development in freshwater ecosystems impacted by agriculture, industry, or waste water, the aquatic life stages of emerging insects are regularly exposed to a broad range of anthropogenic contaminants. Contaminants with low toxicities can potentially bioaccumulate in the developing aquatic life stages of emerging insects with minimal effect on emergence success and, when retained by the emerging adult insects after metamorphosis, can be transported into adjacent terrestrial ecosystems . A wide range of contaminants have been observed to be retained by the adult aquatic insects after metamorphosis, for example, some pesticides, metals, metal-based nanoparticles, pharmaceuticals, polychlorinated biphenyls (PCBs), per- and polyfluorinated alkyl substances, and polycyclic aromatic hydrocarbons (PAHs). After successful emergence, these insects serve as important nutritional sources for spiders, lizards, birds, and bats in adjacent terrestrial food webs . Retention of contaminants by emerging insects therefore has the potential to increase the dietary exposure of terrestrial insectivores, including species of high conservation value .…”
Section: Introductionmentioning
confidence: 99%
“…Neonicotinoid insecticides, however, break away from the trend toward reduced environmental persistence and are found in freshwater ecosystems globally (Morrissey et al, 2015). The ubiquitous presence of insecticides in freshwater ecosystems, even for brief exposure periods during run‐off or spray drift events, has the potential to negatively impact linked aquatic–terrestrial food webs through emerging aquatic insects (Bundschuh et al, 2022; Kraus et al, 2021; Kraus, 2019; Schulz & Liess, 2001; Tooker & Pearsons, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now aquatic–terrestrial contaminant transfer has been reported for several classes of contaminants, including metals (Chételat et al, 2008; Wesner et al, 2017), metal‐based nanoparticles (Bundschuh et al, 2019), pharmaceuticals (Previšić et al, 2021), halogenated organic pollutants (Liu et al, 2018), and some fungicides and herbicides (Roodt et al, 2022). In the terrestrial environment, these contaminants can enter the food web and potentially result in detrimental effects on consumers, such as prey avoidance or sublethal effects (Koch et al, 2020; Kraus et al, 2014, 2021; Richmond et al, 2018). Furthermore, exposure to insecticides during the development of emerging aquatic insects can impact the terrestrial recipient food web through changes in insect emergence phenology and productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation